A Non-condensing Thermal Compression Power Generation System. (September 2017) - McGrail, B.P.; Jenks, J.J.; Abrams, W.P.; Motkuri, R.K.; Phillips, N.R.; Veldman, T.G.; Roberts, B.Q.
Abstract: Organic Rankine cycle (ORC) systems have attracted interest for more than three decades due to advantages in operation at lower working temperature, low maintenance requirements, and relative simplicity (fewer components). In theory, these advantages should make ORC technology more economically attractive for the small and medium power scales (10 kW to 10 MW). Unfortunately, the theoretical promise of ORC systems for power generation has been realized at only a relatively small fraction of the potential market. Although there are a number of reasons for the low utilization of ORC technology, the root cause is directly tied to the relatively low heat-to-power conversion efficiency (2 to 7% typically) and high cost of specially designed expander–generator equipment that is up to 60% of total system cost [1]. The resulting high cost of the power produced just does not make economic sense except in very specialized situations where on-site power is needed but unavailable (at any cost) or where local generation costs are well above regional averages. The overarching objective of the work presented here is to break this paradigm by developing and demonstrating a new harmonic adsorption recuperative power cycle (HARP) system that offers 40% more efficient power generation as compared with a standard ORC system and estimated electric power production costs at very competitive rates below $0.10/kWh.